2012
DOI: 10.1158/0008-5472.sabcs12-p2-01-02
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-01-02: Circulating Tumor Cells (CTC) may Express HER2/neu in Patients With Early HER2/neu Negative Breast Cancer – Results of the German SUCCESS C Trial

Abstract: The number of detected CTC was distributed as follows: 1 CTC (n=76; 55.9%), 2 CTCs (n=35; 25.7%), 3 CTCs (n=13; 9.6%), 4 CTCs (n=7; 5.2%) and 5 CTCs (n=5; 3.7%). HER2/neu staning of CTCs was not detectable or weak in 26.5% (n=36) and 4.4% (n=6) of CTC positive patients respectively and therefore categorized as HER2/neu negative. In 32.4% of the CTC-positive patients (n=44), we detected moderate and in 36.8% (n=50) strong HER2/neu-staining of 1 CTC per sample. No association was found between CTCs or the HER2/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…4042 The adjuvant phase III SUCCESS-B trial of early HER2 + breast cancer assessed baseline CTCs; patients were considered to have HER2 + CTCs if they had 1 or more detectable CTC with strong staining. 43 Results showed a discordance similar to that seen in other studies; of the 257 patients with HER2 + breast cancer with detectable CTCs, only 57.2% were determined to have HER2 + CTCs and 21.4% were questionable (having moderate HER2 staining). Data are pending on survival and the potential role of HER2 + CTCs in determining treatment efficacy.…”
Section: Prognostic and Predictive Value Of Ctc Detectionsupporting
confidence: 78%
“…4042 The adjuvant phase III SUCCESS-B trial of early HER2 + breast cancer assessed baseline CTCs; patients were considered to have HER2 + CTCs if they had 1 or more detectable CTC with strong staining. 43 Results showed a discordance similar to that seen in other studies; of the 257 patients with HER2 + breast cancer with detectable CTCs, only 57.2% were determined to have HER2 + CTCs and 21.4% were questionable (having moderate HER2 staining). Data are pending on survival and the potential role of HER2 + CTCs in determining treatment efficacy.…”
Section: Prognostic and Predictive Value Of Ctc Detectionsupporting
confidence: 78%
“…Pantel et al have shown that the HER2 status in CTCs varies with respect to the primary tumor. 39 Specifically, HER2+ CTCs may be observed in ∼30% of samples obtained from HER2-origin. 40 DNA fluorescence in situ hybridization (FISH) was carried out to evaluate the HER2 status of isolated CTCs.…”
Section: Fish Analysismentioning
confidence: 99%
“…This is in accordance with previous findings that heterogeneity of the HER2 status is evident in CTCs as compared to the primary tumor. 39…”
Section: Fish Analysismentioning
confidence: 99%
“…terion was the HER2-negative nature of the primary tumour [60]. In total 6.9 % of the patients exhibited CTC.…”
Section: Number Of Events (%)mentioning
confidence: 98%
“…B. HER2-negative Patientinnen im Rahmen der Tumorprogression HER2-positive Metastasen entwickeln. Aus diesem Grund wurde in der SUCESS-C-Studie, deren Einschlusskriterium HER2-Negativität des Primärtumors war, der HER2-Status der zirkulierenden Tumorzellen (CTC) als potenzieller Ausgangspunkt einer späteren Metastasierung untersucht [60]. Insgesamt wiesen 6,9 % der Patientinnen CTC auf.…”
Section: Her2-status Zirkulierender Tumorzellen Im Rahmen Der Successunclassified